PENGARUH TIPE TANAH TERHADAP KOMUNITAS RAYAP TANAH - Ginuk Sumarni; Agus lsmanto (Jurnal Penelitian Hasil Hutan, 1987)
Beside temperature  and humidity,  soil type is an important factor  that effects  termite population  size.  From  three types of soil selected for the study  (association  of dark grey alluvial and greyish  brown,  grey regosol and association  of  low peat  glei and grey alluvial),  three  termite species, namely Microtermes insperatus Kemner, M. incertoides Holmgren and Macrotermes  gilvus (Hagen) were observed.  These three species of termite inhabited  the low peat  glei and grey alluvial soil.  In  the association  of  dark  grey alluvial  and greyish  brown  soil, only  M.  gilvus  was observed.  This same species of  termite  was also spotted  the grey regosol soil.The number of termite individuals found in the three  types  of soil  were obviously  different. The greatest  number  were observed  in the association  of low peat  glei and grey alluvial soil.